Characterization of Sleeping Beauty Transposition and Its Application to Genetic Screening in Mice - Horie, Kyoji (Mol Cell Biol, 2003)
The use of mutant mice plays a pivotal role in determining the function of genes, and the recently reported germ line transposition of the Sleeping Beauty (SB) transposon would provide a novel system to facilitate this approach. In this study, we characterized SB transposition in the mouse germ line and assessed its potential for generating mutant mice. Transposition sites not only were clustered within 3 Mb near the donor site but also were widely distributed outside this cluster, indicating that the SB transposon can be utilized for both region-specific and genome-wide mutagenesis. The complexity of transposition sites in the germ line was high enough for large-scale generation of mutant mice. Based on these initial results, we conducted germ line mutagenesis by using a gene trap scheme, and the use of a green fluorescent protein reporter made it possible to select for mutant mice rapidly and noninvasively. Interestingly, mice with mutations in the same gene, each with a different insertion site, were obtained by local transposition events, demonstrating the feasibility of the SB transposon system for region-specific mutagenesis. Our results indicate that the SB transposon system has unique features that complement other mutagenesis approaches.